Sistem Pendukung Keputusan SNMPTN Jalur Undangan Dengan Metode Electre - Lidia K Simanjuntak; Tessa Y M Sihite; Mesran Mesran; Nuning Kurniasih; Yuhandri Yuhandri (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2018)
All colleges each year organize the selection of new admissions. Acceptance of prospective students in universities as education providers is done by selecting prospective students based on achievement in school and college entrance selection. To select the best student candidates based on predetermined criteria, then use Multi-Criteria Decision Making (MCDM) or commonly called decision support system. One method in MCDM is the Elimination Et Choix Traduisant la Reality (ELECTRE). The ELECTRE method is the best method of action selection. The ELECTRE method to obtain the best alternative by eliminating alternative that do not fit the criteria and can be applied to the decision SNMPTN invitation path.